2022
DOI: 10.5829/ije.2022.35.10a.19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Steel Fiber Reinforced Geopolymer Concrete Made of Recycled Materials

Abstract: In the last few decades, the geopolymer concrete presented an evolution in civil engineering field. The current study aims to produce a low cost steel fiber reinforced geopolymer concrete with an ecceptable tensile properties. The experimental program aims to investigate the tensile behaviour of geopolymer concrete reinforced with steel fiber and made of recycled materials. The primary ingredients of the steel fiber reinforced geopolymer concrete in this study were waste materials. The recycled steel fiber was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The beams were subjected to a successive cycle of loading and unloading (repeated loading) (7). Through this type of loading, as shown in Figure 3.…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The beams were subjected to a successive cycle of loading and unloading (repeated loading) (7). Through this type of loading, as shown in Figure 3.…”
Section: Experimental Workmentioning
confidence: 99%
“…Both ordinary concrete and geopolymer concrete are weak under tensile stresses and for this reason; the concrete in tension is neglected in many international codes and depends in totally on the strength of steel reinforcement to resist the tensile strength in structural members. While plain concrete tensile strength enhanced significantly by adding steel fibers to the concrete mix (7). The use of geopolymer cement can reduce carbon dioxide emissions by 44-64% compared to Portland cement (8).…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadi and Bagheripour [7] studied the engineering properties of self-compressing lightweight concrete (SCLWC) after adding fibers to it and found that the compressive strength was improved by adding 1% fine steel fibers. Goaiz et al [8], Mohammed and Kadhim [9] showed that adding fiber increased compressive strength. A study by Varghese et al [10] showed that carbon fiber-reinforced concrete samples had better residual shear strength than others.…”
Section: Introductionmentioning
confidence: 99%
“…The concrete industry, heavily reliant on non-renewable resources and CO2-intensive processes, presents a significant opportunity for sustainability through the exploration of alternative materials (1). Concrete, a primary construction material, typically contains 10-15% Portland cement (OPC), with the remainder being aggregates, water, and other additives.…”
Section: Introductionmentioning
confidence: 99%